2014
DOI: 10.3791/51909
|View full text |Cite
|
Sign up to set email alerts
|

Methylnitrosourea (MNU)-induced Retinal Degeneration and Regeneration in the Zebrafish: Histological and Functional Characteristics

Abstract: Retinal degenerative diseases, e.g. retinitis pigmentosa, with resulting photoreceptor damage account for the majority of vision loss in the industrial world. Animal models are of pivotal importance to study such diseases. In this regard the photoreceptor-specific toxin N-methyl-N-nitrosourea (MNU) has been widely used in rodents to pharmacologically induce retinal degeneration. Previously, we have established a MNU-induced retinal degeneration model in the zebrafish, another popular model system in visual res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…In recent studies, visual acuity measurements have shown decreasing visual function until day 3, followed by complete restoration of visual acuity on day 30. This is consistent with the histological degenerative and regenerative changes observed after MNU administration, with maximum apoptosis occurring on day 3 [137]. Notably, significant advancement has been achieved in elucidating the cell signal transmission mechanism that promotes the transition of Müller glia into MGPCs.…”
Section: Regenerative Mechanisms In Retinitis Pigmentosa (Rp) Indusupporting
confidence: 81%
“…In recent studies, visual acuity measurements have shown decreasing visual function until day 3, followed by complete restoration of visual acuity on day 30. This is consistent with the histological degenerative and regenerative changes observed after MNU administration, with maximum apoptosis occurring on day 3 [137]. Notably, significant advancement has been achieved in elucidating the cell signal transmission mechanism that promotes the transition of Müller glia into MGPCs.…”
Section: Regenerative Mechanisms In Retinitis Pigmentosa (Rp) Indusupporting
confidence: 81%
“…Moreover, the observation that cones are also killed by MNU toxicity does not correspond to cone degeneration in RP patients, since the demise of this population occurs in a secondary wave after rod death. A higher susceptibility of the rod photoreceptors to MNU has been reported in arvicanthis and zebrafish which are both conedominant species (Boudard et al, 2010;Tappeiner et al, 2013;Maurer et al, 2014). Therefore, it is highly possible that the cone photoreceptors might be rather protected from the MNU effects than saved by the EPO.…”
Section: Discussionmentioning
confidence: 97%
“…Alkylating agents targeting photoreceptor cells such as MNU rapidly induce retinal damage through apoptosis in many animal species, including mice [29,30]. Such damage usually develops into benign and malignant tumors several months after exposure to MNU and rapidly causes specific photoreceptor cell death [14,31]. This resulted in a loss of retinal layer structure and marked retinal thinning, which was observed in a concentration-dependent manner after exposure to MNU [32].…”
Section: Discussionmentioning
confidence: 99%
“…MNU is as a pharmacological substance used to induce retinal degeneration in animal models [14]. Therefore, in animal experiments, we induced retinal damage with MNU to determine whether CA-HE50 has a protective effect against retinal damage.…”
Section: Protective Effect Of Ca-he50 In a Model Of N-methyl-n-nitrosmentioning
confidence: 99%